Multigenerational experimental simulation of climate change on an economically important insect pest. Issue 23 (27th October 2020) - Schneider, David; Ramos, Alejandra G.; Córdoba‐Aguilar, Alex
Abstract: Long‐term multigenerational experimental simulations of climate change on insect pests of economically and socially important crops are crucial to anticipate challenges for feeding humanity in the not‐so‐far future. Mexican bean weevil Zabrotes subfasciatus, is a worldwide pest that attacks the common bean Phaseolus vulgaris seeds, in crops and storage. We designed a long term (i.e., over 10 generations), experimental simulation of climate change by increasing temperature and CO2 air concentration in controlled conditions according to model predictions for 2100. Higher temperature and CO2 concentrations favored pest's egg‐to‐adult development survival, even at high female fecundity. It also induced a reduction of fat storage and increase of protein content but did not alter body size. After 10 generations of simulation, genetic adaptation was detected for total lipid content only, however, other traits showed signs of such process. Future experimental designs and methods similar to ours, are key for studying long‐term effects of climate change through multigenerational experimental designs. Abstract : This multigenerational simulation of climate change demonstrates how an economically important pest of the bean seeds; the Mexican bean weevil, will be leaner, fitter and show genetic resilience under the conditions predicted for 2100.